Cardiopulmonary Exercise Testing in Children and Adolescents With Dystrophinopathies: A Pilot Study. Issue 3 (2015) - Bartels, Bart; Takken, Tim; Blank, A. Christian; van Moorsel, Huib; van der Pol, W. Ludo; de Groot, Janke F.
Abstract : Purpose: To determine exercise response during cardiopulmonary exercise testing in children and adolescents with dystrophinopathies. Methods: Exercise response on the cardiopulmonary exercise test (CPET) was compared with a standard care test protocol. Results: Nine boys (aged 10.8 ± 4.7 years) with Becker muscular dystrophy (n = 6) and Duchenne muscular dystrophy (n = 3) were included. The feasibility of the CPET was similar to a standard care test protocol, and no serious adverse events occurred. In 67% of the subjects with normal or only mildly impaired functional capacity, the CPET could be used to detect moderate to severe cardiopulmonary exercise limitations. Conclusions: The CPET seems to be a promising outcome measure for cardiopulmonary exercise limitations in youth with mild functional limitations. Further research with larger samples is warranted to confirm current findings and investigate the additional value of the CPET to longitudinal follow-up of cardiomyopathy and the development of safe exercise programs for youth with dystrophinopathies. Abstract : The Cardiopulmonary Exercise Test is reported to show promise as an outcome measure for cardiopulmonary exercise limitations in youth with muscular dystrophy who have mild functional limitations.